Glioblastoma Current Evidence - Agrawal, Amit; Singh Kunwar, Daulat (IntechOpen, 2023)
Glioblastoma (GBM) is a common and aggressive brain cancer with features of necrosis and endothelial proliferation in the histopathologic examination. Its presentation and management depend on tumor location, size, grade, and underlying histopathological characteristics. GBM tumors have clinical features of increased intracranial pressure, focal neurological deficits, or seizures (generalized or partial) with rapid progression. This book discusses GBM and its diagnosis, treatment, and management.